Analysis on Binding Energy and Auger Parameter for Estimating Size and Stoichiometry of ZnO Nanorods. (2nd October 2011) - Bera, Santanu; Dhara, Sandip; Velmurugan, S.; Tyagi, A. K.
Abstract : ZnO nanorods prepared through chemical vapor deposition technique are characterized by microscopic and X-ray photoelectron spectroscopy (XPS) techniques to correlate the effects of size on the binding energy of Zn 2p3/2 photoelectrons. A positive shift in Zn 2p3/2 -binding energy as compared to that in bulk ZnO is assumed to be the effect of size of ZnO tips. The shift in binding energy has been explained in terms of relaxation energy in the photoemission process. Simultaneously, Auger parameter of the nanorods is evaluated for stoichiometric composition. The extra peak in O1s spectrum of nanorods is explained as adsorbed O-bearing species or surface contaminants.